Autofluorescence characterisation of isolated whole crypts and primary cultured human epithelial cells from normal, hyperplastic, and adenomatous colonic mucosa. Issue 7 (23rd June 2005) - DaCosta, R S; Andersson, H; Cirocco, M; Marcon, N E; Wilson, B C
Abstract : Background/Aims: In vivo autofluorescence endoscopic imaging and spectroscopy have been used to detect and differentiate benign (hyperplastic) and preneoplastic (adenomatous) colonic lesions. This fluorescence is composed of contributions from the epithelium, lamina propria, and submucosa. Because epithelial autofluorescence in normal and diseased tissues is poorly understood, this was the focus of the present study. Methods: Whole colonic crypts were isolated, and short term primary cultures of epithelial cells were established from biopsies of normal, hyperplastic, and adenomatous colon. Autofluorescence (488 nm excitation) was examined by confocal fluorescence microscopy. Fluorescently labelled organelle probes and transmission electron microscopy were used to identify subcellular sources of fluorescence. Results: Mitochondria and lysosomes were identified as the main intracellular fluorescent components in all cell types. Normal and hyperplastic epithelial cells were weakly autofluorescent and had similar numbers of mitochondria and lysosomes, whereas adenomatous (dysplastic) epithelial cells showed much higher autofluorescence, and numerous highly autofluorescent lysosomal (lipofuscin) granules. Conclusions: Short term primary cell cultures from endoscopic biopsies provide a novel model to understand differences in colonic tissue autofluorescence at the glandular (crypt) and cellular levels. The differences between normal, hyperplastic, and adenomatous epithelial cells are attributed in part to differences in the intrinsic numbers of mitochondria and lysosomes. This suggests that the detection of colonic epithelial fluorescence alone, if possible, may be sufficient to differentiate benign (hyperplastic) from preneoplastic and neoplastic (adenomatous) colonic intramucosal lesions during in vivo fluorescence endoscopy. Furthermore, highly orange/red autofluorescent intracellular granules found only in dysplastic epithelial cells may serve as a potential biomarker.